A formação permanente de professores de Geografia no contexto da implementação do currículo da cidade de São Paulo - Oddone, Andrea Laranjeira (2023)
This research aims to contribute to other investigations related to the teachers’ training in the context of democratic management. This research aims to analyze the professional development of geography teachers of the Municipal Education Network (RME) of São Paulo in the context of the City Curriculum, based on Paulo Freire's pedagogy. We take Freire (2001) as our main theoretical reference, discussing the politics and the social quality of education. Authors such as Canário (2008), Candau (1997) and Lima (2016), aligned with Freire’s ideas, also made important contributions to this investigation. Correlated studies conducted on the subject of this study were also sought. The production and data analysis procedures had a qualitative approach and included: a) analysis of official documents of the city of São Paulo that record the concepts and norms for teacher education, the Political-Pedagogical Project (PPP) of the schools - object of this study, the City Curriculum; b) semi-structured interviews with Geography teachers of Freguesia do Ó/Brasilândia DRE. tThe results showed the understanding that the curricular implementation policies must consider the territories where they are put into practice and, regarding teacher education, they must seek to dialogue with those subjects, from a reflection-on-practice point of view, and differently from the current paths of teacher education implemented by the Municipal Education Network of São Paulo, in the context of the effectiveness of the City Curriculum, which is opposed to the teacher education proposal of Paulo Freire's administration (1989- 1992)